Redesain Kewenangan Mahkamah Konstitusi dalam Penyelesaian Sengketa Perselisihan Hasil Pemilihan Umum Presiden dan Wakil Presiden di Indonesia - Harry Setya Nugraha (Fakultas Hukum Universitas Islam Indonesia, 2015)
The implementation of Presidential election in Indonesia cannot be regarded as democratic since the designof dispute settlement of the Presidential Election by the Constitutional Court is not planned ideally. Thus, this study examines some research problems underlying the issue: first, what is the urgency of redesigning the authority of the Constitutional Court in resolving disputes of Presidential Election in Indonesia? and second, how is the ideal concept of dispute settlement in order to achieve a democratic election? The method used in this research is normative juridical of legislation approach and concept approach. The result of the study revealed that: first, it is highly urgent to redesign the authority of the Constitutional Court in the dispute settlement of PHPU of President and Vice President in Indonesia to democratize the election as well to find alternative solutions to the elections that could provide legal certainty, fairness and expediency. Second, redesigning the authority of the Court in resolving disputes of the Presidential PHPU includes the expansion of the definition of disputed election results; designing the benchmark of structured systematic and massive electoral violations; and redesigning the time given by the Court in resolving electoral disputes.